2006
DOI: 10.1007/s00701-006-0767-8
|View full text |Cite
|
Sign up to set email alerts
|

Anton’s syndrome due to a giant anterior fossa meningioma. The problem of routine use of advanced diagnostic imaging in psychiatric care

Abstract: We present a case of blindness and Anton's syndrome in a psychiatric patient with late diagnosis of a giant frontal meningioma. The criteria for advanced diagnostic imaging in the psychiatric population are discussed. We conclude that MR or CT scan is indicated in psychiatric in-patients who fail to improve with standard psychiatric treatment. This strategy should be submitted to a cost-benefit analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…8,10 It has been reported that a patient with Anton's syndrome, caused by a giant frontal fossa meningioma involving the corpus callosum, became aware of visual deficits after the removal of the bifrontal meningioma. 4 This finding further indicates that precortical lesions of the visual pathway can also be responsible for Anton's syndrome. The focus that was responsible for our case was located in the bilateral optic radiation, rather than the bilateral occipital lobes; Anton's syndrome involving this site is extremely rare.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…8,10 It has been reported that a patient with Anton's syndrome, caused by a giant frontal fossa meningioma involving the corpus callosum, became aware of visual deficits after the removal of the bifrontal meningioma. 4 This finding further indicates that precortical lesions of the visual pathway can also be responsible for Anton's syndrome. The focus that was responsible for our case was located in the bilateral optic radiation, rather than the bilateral occipital lobes; Anton's syndrome involving this site is extremely rare.…”
Section: Discussionmentioning
confidence: 90%
“…Anton's syndrome is a rare neuropsychiatric syndrome that is characterized by cortical blindness and anosognosia with visual confabulation, without global cognitive impairment. [1][2][3][4] Anton's syndrome (also called Anton-Babinski symptom) was named by Gabriel Anton and Joseph Babinski, and is characterized by confabulation as a result of the denial of vision loss. 6 That is, patients with Anton's syndrome behave as if they can see despite obvious visual loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relatively small number of reported cases with schizophrenia and corpus callosum abnormalities, along with the uncertain prevalence of such anomalies in the normal population, does not allow establishing a causal relationship [2, 3]. Also tumors of the corpus callosum can be present with dementia, depression, schizophrenia, and psychosis [8–14]. Usually the tumors are so big that it is not easy to assess whether the primary cause of symptoms is the damage of corpus callosum or the involvement of other adjacent structures.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions of the central nervous system may present with symptomatology suggestive of psychiatric conditions. This has been dramatically demonstrated previously with psychiatric presentations of large anterior cranial fossa meningiomas, leading to the recommendation that patients presenting with psychiatric syndromes in middle to later life and those refractory to treatment should undergo imaging to avoid delay of appropriate treatment [1, 2]. With the ready availability of high-resolution neuroimaging, patients with persistent or severe psychiatric symptoms should be considered for radiological and/or electrophysiological investigation.…”
mentioning
confidence: 99%